Peningkatan Hasil Belajar Melalui Model PBL Dengan Identifikasi Dan Perbandingan Praktik Keseharian Pada Materi Yesus Mewartakan Kerajaan Allah Di Kelas IV UPTD SDN 071075 Hiligara Kota Gunungsitoli - Anemala Gea (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Anemala Gea, 2023. Improving learning outcomes through the PBL model by identifying and comparing daily practices in the material of Jesus preaching the kingdom of God in class IV UPTD SDN 071075 Hiligara, Gunung Sitoli City. Classroom Action Research Report. This research aims to (1) find out how the application of the Problem Based Learning (PBL) model can increase students' learning motivation on the material that Jesus preached the kingdom of God through parables in class IV UPTD SDN 071075 Hiligara, Gunungsitoli City. (2) knowing how the application of the Problem Based Learning (PBL) model can increase students' learning motivation on the material on the Miracles of Jesus in class IV UPTD SDN 071075 Hiligara, Gunungsitoli City (3) Looking for the right solution to overcome the obstacles faced by teachers in learning (4) ) Improve students' skills in solving daily life problems. The research subjects were Class IV students of UPTD SD Negeri 071075 Hiligara, Gunungsitoli City. The research object is that the Problem Based Learning (PBL) model can improve student learning outcomes. The form of this research is classroom action research with a cyclical model, each cycle consists of four stages, namely, planning, implementing action, observing and reflecting. At the observation stage, the researcher collects data by observing student activities guided by the Pancasila Student Profile rubric ( P3) through the use of the Problem Based Learning (PBL) Model. The observation results from 6 students in Cycle I averaged 71%, and in Cycle II it increased to an average of 81%. The learning outcomes in cycle I averaged 75.54%, and in cycle II increased to an average of 86.37%. From this increase, it can be seen that it is 10.83% higher than before.